Analisis Kualitas Jamur Krispy Berbasis Kepuasan Konsumen (Studi Kasus: IKM Berkah Cinta Trenggalek) - Ulfa Nur Aida; Yuli Wibowo; Bambang Herry Purnomo (Agroindustrial Technology, University of Trunojoyo Madura, 2019)
Small-Medium Enterprise (SME) Berkah Cinta Trenggalek (BCT) is a that produces snacks in the form of crispy mushrooms with the brand name of the “Jamur Mantan”, with the main sales in the Kediri regency. Was established in 2017, so this SME can classified as a new home industries and have faced some business competitors with similar snacks produced. Therefore, it is important to created customer satisfaction by improved quality of product. The purposed of this study is to know the level consumer satisfaction crispy mushrooms, the indicators of each product quality attribute that are considered important by consumers for the quality improvement processed, the results of the analysis of technical specifications that have high relevancy in the effort to formulate recommendation for improving the quality of the crispy mushrooms, formulate recommendation that can be used for the processed of improving the quality of the crispy mushroom SME BCT. The data analysis method used to measured the level customer satisfaction is the Customer Satisfaction Indes (CSI), Importance Performance Analysis (IPA) to determined the performance level of each atribute, and Matrix Diagram to find out the relationship between technical speafications of making crispy mushrooms and low performance quality indicators. The results of this study was indicated that level of customer satisfaction with crispy mushrooms from the CSI method as 79,73%. The analysis used IPA obtained 5 quality atribute indicators that performed low with hight customer expectation. So, this 5 indicators needed further analysis used the Matrix Diagram, the results obtained showed 3 that the formulate recomendations that can be used for the quality improvement. There are improving design product by re-design products, lre-design for the right compositions to produced flavor that tasty and consistent, and regulates the use of cooking oil.